Evaluating the impact of polycythemia vera on retinal and optic nerve head microvascularity: An OCTA study - Meryem Feyza Cicek; Turker Oba; Abdullah Ağın; Mesut Ayer; Feyza Onder (Indian Journal of Ophthalmology)
Purpose: This study aims to assess the impact of polycythemia vera (PV) on retinal and optic nerve head (ONH) vessel density (VD) parameters, macular ganglion cell complex (mGCC) thickness, and retinal nerve fiber layer (RNFL) thickness compared to healthy controls. Methods: Forty eyes of 20 patients with PV and 40 eyes of 20 age-gender-matched healthy controls underwent comprehensive ophthalmologic assessments and optic coherence tomography angiography (OCTA). RNFL and macular GCC measurements were obtained simultaneously with vascular parameters by AngioVue OCTA using the single-scan protocol. Peripapillary VD was examined across eight sectors, whereas parameters including RNFL, GCC, and macular VD were analyzed in four quadrants. Results: Patients with PV exhibited significant reductions in the average RNFL thickness (P = 0.014) and RNFL thickness in superior (P < 0.001) and inferior (P = 0.003) quadrants compared to controls. Additionally, mGCC thickness in all quadrants significantly reduced in the PV group (P < 0.001). ONH VD parameters, including whole-image VD (P < 0.001) and peripapillary VD (P < 0.001), were significantly reduced in patients with PV. Similarly, macular VD parameters were significantly lower in the PV group (P < 0.001). Conclusion: This study highlights substantial vascular and structural alterations in the retina and ONH of patients with PV compared to healthy controls. These changes likely stem from microvascular dysfunction associated with PV. These findings suggest further research to understand the underlying mechanisms and develop targeted therapeutic strategies for managing ocular complications in patients with PV.